A new and a described species of Cystiphora (Diptera: Cecidomyiidae) from Japan, with reference to geographically diversified intraspecific populations of C. taraxaci and its host range expansion from native Japanese to alien and hybrid species of Taraxacum (Asteraceae). Issue 3 (20th July 2021) - Yukawa, Junichi; Kim, Wanggyu; Nishino, Takako; Minami, Tsuneo; Yamauchi, Satoshi; Ogawa, Makoto; Ohara, Kenji
Abstract: Two species of Cystiphora (Diptera: Cecidomyiidae) are newly recorded from Japan. A gall midge that induces leaf galls on Taraxacum species (Asteraceae) is identified as Cystiphora taraxaci (Kieffer). Another gall midge that is responsible for leaf galls on Sonchus brachyotus (Asteraceae) is described as a new species under the name Cystiphora hachijounae Yukawa and Kim based on its incised hypoproct of male terminalia and some of the pupal characteristics. Genetic analysis supported the species identifications and indicated that the Palearctic C. taraxaci has long existed in Japan. It has been diversifying geographically into intraspecific populations since at least 2.57 Ma. Our current study argues against the recent invasion of Japan by alien C. taraxaci at the time of multiple introductions of European Taraxacum species to Japan for use as food (seed oil), forage and greening material during the late 19th century. Genetic analysis of gall‐bearing Taraxacum plants collected from various localities in Japan indicates that most of them were alien or hybrid plants, while native Japanese species were rare, and these plants exhibited polyploidy from 2x to 5x. Cystiphora taraxaci is considered to have expanded its host range from native Japanese to alien and hybrid species of Taraxacum without regard to polyploidy. Abstract : This article records a new and a described species of Cystiphora from Japan for the first time. It reports that Cystiphora taraxaci has long existed in Japan as a Palearctic species and has geographically diversified into intraspecific populations by expanding its host range from native Japanese to alien and hybrid species of Taraxacum (Asteraceae).